Levodopa Challenge Test Predicts STN-DBS Outcomes in Various Parkinson's Disease Motor Subtypes: A More Accurate Judgment. (21st October 2021) - Zheng, Zijian; Yin, Zixiao; Zhang, Bohan; Fan, Houyou; Liu, Dan; Zhou, Yuancheng; Duan, Jian; Zhou, Dongwei; Wu, Xi; Lu, Guohui
Abstract : Background . The relationship between the levodopa challenge test (LDCT) and postoperative subthalamic nucleus-deep brain stimulation (STN-DBS) benefits is controversial in patients with Parkinson's disease (PD). We aim to evaluate the value of total levodopa response (TLR) and symptom levodopa response (SLR) in predicting postoperative improvement in different PD motor subtypes. Methods . Studies were split into a training set (147 patients) and a validation set (304 patients). We retrospectively collected data from 147 patients who received the Unified Parkinson's Disease Rating Scale- (UPDRS-) III and the Parkinson's Disease Questionnaire- (PDQ-) 39 evaluation. Patients were classified into tremor-dominant (TD), akinetic-rigid-dominant (AR), and mixed (MX) groups. Clinically important difference (CID) was employed to dichotomize DBS effects. For patients in each subtype group from the training set, we used the correlation and receiver operator characteristic (ROC) curve analyses to explore the strength of their relations. Areas under the curve (AUCs) were calculated and compared through the DeLong test. Results developed from the training set were applied into the validation set to predict postoperative improvement in different PD motor subtypes. Results . In the validation cohort, TLR significantly correlated with postoperative motor (p < 0.001 ) and quality of life (QOL) (p < 0.001 ) improvement in the MX group. The AUC between TLR and UPDRS-III (TU) is 0.800. The AUC between TLR and PDQ-39 (TP) is 0.770. An associated criterion in both TU and TP is around 50%. In the AR group, strong correlation was only found in SLR and PDQ-39 (SP) (p < 0.001 ). And the AUC of SP is significantly larger than that in TLR and PDQ-39 (TP) (p = 0.034 ). An associated criterion in SP is around 37%. No significant correlation was found in the TD group. Conclusions . We provide a more accurate judgment for LDCT. TLR strongly correlated with postoperative UPDRS-III and PDQ-39 improvement in MX patients. A TLR > 50 % may indicate a higher possibility of clinically meaningful benefits from STN-DBS comparing to medication only. SLR can well predict QOL improvement in AR patients. Similarly, a SLR > 37 % may indicate a higher possibility of clinically significant benefits from STN-DBS. LDCT provides limited information for TD patients.